Dynamical Behavior of Secondary Dengue Infection Model - Tay, Chai Jian (Communication in Biomathematical Sciences, 2019)
With the increase of dengue cases in the last decades, efforts on controlling the dengue disease have been carried out. Dengvaxia, the first dengue vaccine developed by Sanofi Pasteur, was recommended by WHO for trial. The long-term safety follow-up indicates that the vaccine efficacy is higher in seropositive human population and there is an increase risk of severe dengue in vaccinated seronegative human. It is important to understand the dynamical behavior of dengue that includes both the seronegative and seropositive human population before performing vaccination. For such purpose, a secondary dengue infection model is developed and investigated in this paper. The basic reproduction number, Ro is derived and sensitivity analysis is performed to determine the most sensitive parameter in the model. The results indicate that Ro is the most sensitive to the ratio of mosquito to human, dengue transmission from human to mosquito, dengue transmission from mosquito to human and natural mortality of mosquito. It is also found that the ratio of seropositive to seronegative human population is 1.52 for a given set of parameter values at dengue endemic state. This would assist the authorities in deciding the proportion of seropositive and seronegative human population to be vaccinated. Numerical simulation results show that a decline in primary dengue infection is not associated with a decrease in secondary dengue infection. Therefore, the dengue control strategies should produce high efficacy in transmissibility reduction and ultimately reduce the DHF.